Research on Green Barriers and Countermeasures for Chinese Materia Medica Entering ASEAN Countries under the Background of the Belt and Road Initiative - ZHAO, ZHUJUN (Pacific International Journal, 2023)
China-ASEAN Free Trade Area is a huge economy covering 11 countries and 1.9 billion people, and has become the largest free trade area among developing countries. Because of the geographical proximity and cultural similarities between China and ASEAN, and the fact that most ASEAN countries have a high recognition of (Traditional Chinese Medicine (TCM) and prefer to use traditional medicine to treat diseases, there is a large market demand for Chinese Materia Medica (CMM). China-ASEAN Free Trade Area has become an important market for CMM exports. However, ASEAN countries have different degrees of green barriers to CMM exports, mainly including technical trade barriers (TTBs) and non-technical trade barriers (NTBs), and these green barriers have caused a certain impact of the entry of CMM into ASEAN countries. This article proposes legal countermeasures for CMM exports to ASEAN countries to deal with green barriers in terms of Chinese government's diplomacy, trade policy, industrial structure, intellectual property protection, quality of CMM, as well as Chinese enterprises' internal management, dispute resolution, communication and cooperation, with a view to developing the market of CMM in ASEAN countries. In order to speed up the pace of "going out" of CMM.